1993
DOI: 10.1002/hep.1840180120
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular hyporesponsiveness to norepinephrine, propranolol and nitroglycerin in portal-hypertensive and aged rats

Abstract: Most studies testing vasoactive agents in portal-hypertensive rats have been performed in young animals. To assess age-related changes in hemodynamic responses to adrenergic stimuli, we examined (a) responsiveness to norepinephrine (0.14 to 12.0 micrograms.kg-1.min-1) in young (3-mo-old) and aged (9-mo-old) sham-operated and portal-hypertensive rats and (b) response to propranolol (2 and 10 mg.kg-1 body wt), nitroglycerin (3.6 mg.kg-1.min-1) or saline solution in aged portal-hypertensive rats. Aged rats exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…13,15 The responses in MAP to both vasopressin analogues were similar in PVL and SHAM rats. These findings are remarkable, because cardiovascular hyporesponsiveness to vasoconstrictors is a well-known feature of portal hypertension, [23][24][25][26][27][28][29][30] and has also been observed in the present study as systemic and mesenteric hyporesponsiveness to phenylephrine. The mesenteric arterial hyperresponsiveness of PVL rats to vasopressin analogues, as described here in vivo, is unlikely to be the result of increased vasopressin receptor density or affinity, because it is not observed in isolated perfused mesenteric arterial beds of portal hypertensive rats.…”
Section: Discussionsupporting
confidence: 79%
“…13,15 The responses in MAP to both vasopressin analogues were similar in PVL and SHAM rats. These findings are remarkable, because cardiovascular hyporesponsiveness to vasoconstrictors is a well-known feature of portal hypertension, [23][24][25][26][27][28][29][30] and has also been observed in the present study as systemic and mesenteric hyporesponsiveness to phenylephrine. The mesenteric arterial hyperresponsiveness of PVL rats to vasopressin analogues, as described here in vivo, is unlikely to be the result of increased vasopressin receptor density or affinity, because it is not observed in isolated perfused mesenteric arterial beds of portal hypertensive rats.…”
Section: Discussionsupporting
confidence: 79%
“…However, in an experimental study [43], vasopressin proved to be inferior to norepinephrine in terms of improving hepatosplanchnic blood flow. The response to both norepinephrine and vasopressin is blunted in patients with cirrhosis [44, 45]. …”
Section: Resultsmentioning
confidence: 99%
“…From the mid-1980s to the early 1990s, several investigators showed that cardiac contractile reserve is diminished in different rat models of nonalcoholic cirrhosis [16][17][18][19]. Notable is the landmark study of Caramelo and colleagues [17], who infused saline into rats with carbon tetrachlorideinduced cirrhosis.…”
Section: Systolic Dysfunctionmentioning
confidence: 99%